Investing in Human Capital for a Resilient Recovery : The Role of Public Finance - World Bank (World Bank, Washington, DC, 2021)
This Approach Paper considers the role of public finance to build, protect and utilize human capital as countries seek to recover from the COVID-19 (coronavirus) crisis and lay a foundation for inclusive, resilient and sustainable development. The paper defines the problem in relation to human capital outcomes amid the COVID-19 crisis and outlines three areas for action: policy priorities, governance, and fiscal space for building and utilizing human capital. The paper highlights recent innovations and illustrates actionable steps for the short term as well as directions for the longer term, by country context, with the overarching objective of supporting a resilient recovery.